Sacrifice in Judaism and its Challenges to Christian Religious Worship in Nigeria: A Comparative Analysis - Doyah, Clement Tiemo (NIU Journal of Humanities, 2024)
This comparative analysis explores the concept of sacrifice in Judaism and its challenges to Christian religious worship in Nigeria. Sacrifice holds significance in both faith traditions, influencing worship practices in diverse ways. The study focuses on theological implications, historical contexts, and contemporary relevance of sacrificial practices in Judaism and Christianity. In Judaism, sacrifice historically played a central role in religious worship, with rituals of animal offerings serving as means of atonement, thanksgiving, and communion with God. The Hebrew Bible outlines detailed instructions for sacrificial practices, emphasizing purity, obedience, and spiritual intent. However, with the destruction of the Second Temple in 70 CE, the practice of animal sacrifice ceased, leading to new interpretations of sacrifice within Jewish theology. In Nigeria, Christianity has become dominant, coexisting with traditional religious practices involving sacrificial offerings to deities and spirits. The introduction of Christianity in Nigeria has presented challenges to traditional sacrificial practices, resulting in theological debates, cultural conflicts, and shifts in religious identity among Nigerian Christians. The tension between traditional sacrificial rituals and Christian teachings on sacrifice has influenced religious worship practices in Nigeria, showcasing the complexities of religious syncretism and cultural adaptation. This analysis examines the challenges that the concept of sacrifice poses to Christian religious worship in Nigeria, exploring how the legacy of sacrificial practices in Judaism influences Christian perspectives on sacrifice, redemption, and divine worship. By comparing sacrificial traditions in Judaism and Christianity, this study aims to deepen understanding of how religious beliefs, cultural traditions, and theological perspectives interact and evolve in diverse religious contexts. Keywords: Sacrifice, Judaism, Christianity, Religious Worship, Nigeria, Comparative Analysis, Theology, Rituals, Syncretism, Cultural Adaptation